A Study on the Synthesis of 5, 7-Diaryl-1,2,3,4-tetrahydro-2, 4-dioxo-5H-pyrano [2,3-d]pyrimidines (Bangladesh Journal of Scientific and Industrial Research, 2007)
5,7-Diphenyl-1,2,3,4-tetrahydro-2,4-dioxo-5H-pyrano[2,3-d]pyrimidine (4a) has been synthesized in single-step by the condensation of barbituric acid (1) with benzylideneacetophenone (2a) in glacial acetic acid in the presence of phosphorous pentoxide. Reaction of barbituric acid (1) with arylideneacetophenones (2b-d) which gave the corresponding adducts of 5-(1,3-diaryl-1-oxopropyl) pyrimidine (1H, 3H, 5H)-2,4,6-triones (3a-c) previously in 50 % aqueous ethanol which on further reflux in gl. acetic acid in the presence of phosphorous pentoxide also gave the corresponding pyranopyrimidines 5,7-diaryl-1,2,3,4-tetrahydro-2,4-dioxo-5H-pyrano [2,3- d]pyrimidines (4b-d). The structures of the compounds 4a-d were characterized by their UV, IR, 1H NMR and 13C NMR spectral data.Bangladesh J. Sci. Ind. Res. 41(3-4), 119-128, 2006